2023
DOI: 10.1097/ftd.0000000000001067
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Antimicrobial Stewardship Programs Using Therapeutic Drug Monitoring and Pharmacokinetics–Pharmacodynamics Protocols: A Cost-Benefit Review

Abstract: Purpose:Antimicrobial stewardship programs are important for reducing antimicrobial resistance because they can readjust antibiotic prescriptions to local guidelines, switch intravenous to oral administration, and reduce hospitalization times. Pharmacokinetics–pharmacodynamics (PK-PD) empirically based prescriptions and therapeutic drug monitoring (TDM) programs are essential for antimicrobial stewardship, but there is a need to fit protocols according to cost benefits. The cost benefits can be demonstrated by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(1 citation statement)
references
References 122 publications
0
1
0
Order By: Relevance
“… 2 Furthermore, prevention of antimicrobial drugs-related toxicity should also be a potential benefit of ASP, mainly with vancomycin, aminoglycosides and voriconazole. 3 However, despite these data, the first nationwide survey involving 957 Brazilian Adult ICUs found that 52.5 % of these hospitals still do not have ASPs in ICUs. 4 In response to these challenges, a task force was created in Brazil to promote ASPs.…”
mentioning
confidence: 99%
“… 2 Furthermore, prevention of antimicrobial drugs-related toxicity should also be a potential benefit of ASP, mainly with vancomycin, aminoglycosides and voriconazole. 3 However, despite these data, the first nationwide survey involving 957 Brazilian Adult ICUs found that 52.5 % of these hospitals still do not have ASPs in ICUs. 4 In response to these challenges, a task force was created in Brazil to promote ASPs.…”
mentioning
confidence: 99%